PENATALAKSANAAN HIPERPLASIA GINGIVA DISEBABKAN OLEH PENGGUNAAN AMLODIPINE : Sebuah Laporan Kasus - Arni Irawaty Djais; Lilies Anggarwati Astuti (As-Syifaa Jurnal Farmasi, 2014)
Introduction: gingival hyperplasia is a result of administration from some anticonvulsant drugs, immunosuppressants, and calcium channel blockers that well known can cause problems when speaking, mastication, tooth eruption, and aesthetic. Calcium channel blockers are a class of drugs developed for the care of cardiovascular conditions. Some of these drugs can cause gingival enlargement.  Case: A 55-year-old female patient came to Periodontal Department of Hasanuddin University Dental Hospital,Makassar. Patients present with a less comfortable and did not feel confident with the condition of the front of the upper jaw gums since three months ago. These symptoms begin to be felt since taking drugs for hypertension disease with amlodipine with 10 mg 1 time a day. The patient began to feel a change in the form of excessive enlargement of the gums almost the entire upper jaw teeth. Management of Case: Disinfection area of operation, anesthesia with lidocaine 2% of nor epinephrine, marking the pocket using the pocket marker basis, incision using Krickland knife, removal of gingiva using papilla Orban knife and performed by scaling and root planing, periodontal pack was used. Conclusion: Patients who took the drug amlodipine as calcium channel blocker classification in the long-term directly effects the growth of excess gingival tissue, causing gingival enlargement. Keyword: Hyperplasia Gingiva, Amlodipine